METHODOLOGICAL ASPECTS OF THE USE OF BLOCKCHAIN TECHNOLOGY IN DEVELOPMENT BANKS ON THE EXAMPLE OF VNESHECONOMBANK - S. Matveevskii (Вестник университета)
The paper shows the possibilities of the blockchain technology, identified methodological aspects of assessing the possibility of using this technology in the work of the development bank, including Vnesheconombank of the Russian Federation. The author reviewed the main content of the stages of assessing the possibility of using blockchain technology in development bank. It is emphasized that blockchain technology creates a single information field, and in combination with «smart» contracts it allows for the automatic fulfillment of obligations by counterparties. In this regard, DBs have the opportunity to use blockchain technology at certain stages of the project cycle, in the information circulation of the bank itself. The transformation of Vnesheconombank, aimed at «transforming» it into a base for other Russian development institutions, currently makes testing of blockchain technology in Vnesheconombank particularly relevant.